Piagetian theory of cognitive development - S Kazi; E Galanaki (Encyclopedia of child and adolescent development (S. Hupp & J. D. Jewell, Chief Eds.), 2020)
According to Piaget, the attainment of formal operational thought (between the ages of 12 and 15 years) is the final stage of cognitive development, preparing the adolescent to efficiently adapt to the adult world. Piaget regarded formal thinking as propositional, abstract, hypothetico-deductive, combinatory, and reflective, allowing for the conception of both the possible and the real. This entry discusses the fundamental mechanisms that lead to the acquisition of formal thought, along with its specific manifestations. Finally, it presents an overview of the criticism of the Piagetian theoretical standpoint.